A new saprotrophic species of Amanita (Amanitaceae, Agaricales) from Inner Mongolia, China - Liu, Xiaoliang; Bau, Tolgor; Yang, Zhu L. (Phytotaxa, 2021)
A new saprotrophic species in Amanita sect. Lepidella, A. orientisororia, was discovered on lawn and sand dunes in Northeast China. This species was macroscopically characterized by a small white pileus, conical to subconical to pyramidal volval remnants on pileal surface, large broadly ellipsoid to ellipsoid basidiospores measuring 9–13×7–9.5 μm, and the common presence of clamps in all parts of basidiomata. It was described and compared with related species in the genus, based on morphological characteristics and phylogenetic evidence inferred from sequences of the nuclear ribosomal internal transcribed spacer (ITS) and the large subunit of the nuclear ribosomal region (nrLSU).